Before George Eliot Marian Evans and the periodical press - Dillane, Fionnuala (Cambridge studies in nineteenth-century literature and culture, 2014)
"This interdisciplinary study discusses the significance of Evans's work as a journalist, editor and serial-fiction writer in the periodical press from the late 1840s to the late 1850s and positions this early career against critical responses to Evans's later literary persona, George Eliot. Author argues that Evans's association with the nineteenth-century periodical industry, that dominant cultural force of the age, is important for its illumination of Evans's understanding of the formation of reading audiences, the development of literary genres and the cultivation of literary celebrity"--Provided by publisher.